Productive and Receptive Knowledge and Avoidance of Phrasal Verbs: The Case of Saudi Learners of English (المجلة الدولية للبحوث العلمية, 2025)
Recent studies in different parts of the world generally agree that multi-word expressions, including phrasal verbs (PVs), present difficulties for many language learners. The present study not only examines productive and receptive knowledge of PVs among Saudi undergraduates learning English as a foreign language, but also examines learners’ avoidance behavior in the use of PVs. To achieve this, a total of 209 Saudi undergraduates in Saudi universities completed three multiple-choice (MC) tasks to assess their productive and receptive skills, and to measure their PV avoidance behavior. In addition, it investigates the factors that can influence the Saudi learners’ use of PVs relative to their proficiency level, gender, and the semantic nature of PVs (literal-figurative); to determine to what extent these three variables can affect their knowledge and any possible PV avoidance. The results confirm the difficulty pointed out in earlier studies, particularly at the production level. The participants showed better receptive than productive knowledge with an average percentage of correct answers of 72% for the receptive and 59% for the productive tasks. Also, the results suggest that proficiency and the semantic nature of PVs have a statistically significant effect on the use of PVs by Saudi EFL learners for both productive and receptive tasks, while gender is found to have no significant effect. In terms of avoidance, the results show that PV type and proficiency level affect the frequency of PV avoidance. Therefore, it was concluded that the difference between L1 and L2 structure, semantic complexity of phrasal verbs and poor productive knowledge might cause the learners’ avoidance. The study confirms that phrasal verbs present difficulties for many language learners, and consequently deserve more attention by teachers, material designers and the learners.